Wettability and interfacial phenomena in the liquid‐phase bonding of refractory diboride ceramics: Recent developments. Issue 2 (17th December 2021) - Asthana, Rajiv; Sobczak, Natalia; Singh, Mrityunjay
Abstract: Joining and integration technologies are integral to manufacturing of components based on ultrahigh‐temperature ceramics (UHTCs) such as transition metal diborides. Brazing is a particularly attractive joining technique because of its simplicity and versatility, but its use to join the UHTCs demands knowledge of the complex interplay among high‐temperature wettability, interfacial reactions, and chemical and thermoelastic compatibilities. This paper summarizes the research and development activities carried out over the last two decades to characterize the wettability and interfacial phenomena in brazing of refractory diboride ceramics. The contact angle data of various metal alloys on diboride‐based ceramics have been collected and critically evaluated in conjunction with an analysis of the chemistry and structure of the interface to understand the underlying mechanisms and phenomena that govern interface formation. It explores how solid–liquid interactions impact and are impacted by physical, chemical, and mechanical properties of joined materials. It also describes how this knowledge has been successfully utilized to create liquid‐phase bonded diboride‐based joints. The paper concludes with a summary of the current state of the art and highlights integration challenges and future research and technology development needs in the area.